MUSIC THERAPY - Shakarashvili, Marina; Arabuli, Mania (European Scientific Journal, ESJ, 2016)
Scientific and technological progress gives a human being unprecedented capability, but creates challenges too. Numerous new diseases and syndromes are emerging as a result of technological advancements and stress. Art therapy is becoming one of the popular treatment strategies for those conditions. This includes music therapy, as one of the forms of art therapy. Music therapy is interdisciplinary field on the nexus of psychology, neurophysiology, music science, pedagogy and other disciplines. Spectrum of conditions where music therapy can be effectively used is practically unlimited. It has no contradictions and can be used at any age. Clinical studies provide evidence that music can be used effectively during the treatment of different conditions. Those include conditions of nervous system, mental health problems, hypertension, disorders of microcirculatory and hemodynamic systems, cardiovascular conditions, dysfunction of vegetative, digestive and respiratory systems, reduced adaptation capabilities and resistance, pain and autism. This therapy can be beneficial for rehabilitation. Music is also beneficial for elderly patients as it improves mood, increases social contacts and length of life. Effectiveness of music therapy called for the need to create academic professional training programs in this field. Georgia does not have professionals in this field. Only few psychotherapy centers practice art therapy. It is important to train specialist in this filed, as art therapy has number of advantages compared to other treatment strategies. It does not involve pharmaceuticals, does not cause addiction and can be applied to the large spectrum of issues. Furthermore, therapy is not associated with large financial expenditures.